A 96‐week, multinational, randomized, double‐blind, parallel‐group, clinical trial evaluating the safety and effectiveness of bexagliflozin as a monotherapy for adults with type 2 diabetes. Issue 11 (8th August 2019) - Halvorsen, Yuan‐Di C.; Walford, Geoffrey A.; Massaro, Joseph; Aftring, Robert P.; Freeman, Mason W.
Abstract: Aim: To explore the safety and effectiveness of extended exposure to bexagliflozin as a monotherapy for type 2 diabetes. Methods: Adults with diabetes (n = 288) from the USA, Colombia and Mexico were randomized 1:1 to receive bexagliflozin (20 mg) or placebo for 96 weeks. The primary endpoint was the placebo‐adjusted change in HbA1c at 24 weeks. Dosing was continued an additional 72 weeks to assess safety and the durability of the treatment effect. Secondary endpoints measured changes from baseline in body mass and systolic blood pressure (SBP) and diastolic blood pressure (DBP) at week 24, and the change, over study duration, in HbA1c. Results: The placebo‐adjusted change in HbA1c from baseline to week 24 was −0.79% (−8.6 mmol/mol) [95%CI −0.53, −1.06 (−5.8, −11.6), P < .0001]. The unadjusted change from baseline through week 96 was −0.55% (−6.0 mmol/mol) ± 1.184% (12.9) (SD) for the bexagliflozin arm compared with 0.53% (5.8 mmol/mol) ± 1.215% (13.3) for the placebo arm ( P < .0001). Significant decreases in body mass, SBP and DBP could be attributed to bexagliflozin exposure. The incidence of serious adverse events was lower in the bexagliflozin‐treated group (2.8%) than in the placebo group (8.5%). Urinary tract infections occurred less frequently in the active arm (14.5%) than in the placebo arm (20.6%). Conclusions: Bexagliflozin at 20 mg/d was well tolerated and provided a durable, clinically meaningful improvement in glycaemic control over 96 weeks to participants in this phase 2 trial. A substantial reduction in weight and blood pressure was produced by bexagliflozin, with no increase in significant adverse event rates.